Development of athletics instructor training course of Rajabhat University - Yoddumnern, Thanat; Pluemsamran, Tawut; Ann Mahaketa , Ann (Community and Social Development Journal, 2020)
The purpose of this research was to develop a training course for the instructors in athletics of Rajabhat University. The researcher has defined 3 steps of this research follows; 1) Study the circumstance, requirement, and necessity of athletics instructor training course by studying with 30 Physical Education instructors who are in charge of athletics in Rajabhat University in Thailand. Analyzing and synthesizing the past researches that have the same idea with the In-depth Interview. The researcher has been collected the data from 5 specialists in preparing the training athletics course. 2) Creating the athletics instructor training course at Rajabhat University for conducting the practical conference and practical training, and using 5 specialists to create the course and 3) Experimenting and evaluating the athletics instructor training course at Rajabhat University. The objective is organizing the workshop for test the athletics instructor training course of Rajabhat University with the 30 samples who are the instructors by collecting the data and comparing the result before and after participating the athletics instructor training course and collecting the data of the satisfaction of the instructors who participate the athletics instructor training course. The research results are as follows; 1) Survey study of the circumstance, requirement, and necessity of athletics instructor training course at Rajabhat University is indicated that the instructor has the opinion related to the circumstance, requirement, and necessity of athletics instructor training course consists of the athletics knowledge, teaching and learning, and developing athletics student role. In addition, in term of the circumstance, requirement, and necessity of athletics instructor training course indicated that most of the instructor has never participated training course for preparing in conducting the athletics course and the instructor would like to participate the athletics training instructor course. 2) Curriculum development requirement, and necessity of athletics instructor training course at Rajabhat University is indicated that it consists of 4 components. The first component is creating a teaching plan for athletics such as principle and arranging teaching schedule, and writing the teaching plan. The second component is the workshop such as theoretical and practical athletics lesson, preparation of teaching materials, and managing the class. The third component is evaluation of the athletics instructor training course such as methodology and tools for evaluation. The last component is the roles, duties, ethics and desirable characteristics of the instructor. The period of this training course is 16 hours within 2 days. 3) Course assessment requirement, and necessity of athletics instructor training course at Rajabhat University is indicated that the instructors of the course have more knowledge after participating the athletics instructor training course at Rajabhat University with the statistical significance .01 and when considering each component, it is indicated that it is similar to the other component in the level of statistical significance .01. Overall of the satisfaction is the highest level. When considering each subcomponent, it is indicated that the top 3 subcomponents of the satisfaction are the participants have got knowledge from the course, they adapted for their teaching, and the course is consistent with the objective of the curriculum. Study summary the athletics instructor training course at Rajabhat University is indicated that requirement and the course is consistent with the objective of the curriculum.